PENGGUNAAN MEDIA PARAGRAF BOARD UNTUK MENINGKATKAN HASIL BELAJAR IPS PADA MATERI PERJUANGAN BANGSA INDONESIA MELAWAN PENJAJAH - Sri Wulan; Rana Gustian Nugraha (STKIP Sebelas April Sumedang, 2018)
This research is motivated by low activity and learning result of IPS of V student of SDN Pasanggrahan I Sumedang Selatan Subdistrict Sumedang Regency, especially on material of struggle of Indonesia against invaders. To solve the problem, the researcher tried to apply the media of the board paragraph. With the application of the media paragraph board is expected to increase student activity and student outcomes. In this research the researcher formulate research problem that is whether by using media of activity board paragraph and result of study of student of class V SDN Pasanggrahan I Sumedang Selatan District Sumedang Regency on material of struggle of Indonesia against penajajah can be improved. The formulation of research objectives focused on the activities and learning outcomes of IPS. The purpose of this study is to improve the activity and learning outcomes of students by using media paragraph board on the material struggle of the Indonesian nation against invaders. The research design used in the research process is classroom action research (PTK). This classroom action research is carried out in two cycles. Data collection techniques used in this study consisted of observation techniques and test techniques. Instruments used in the form of tests and observation guidelines. Assessment of student activity in the first cycle reached 45% (very good category), 25% (good category), 25% (enough category), 5% (less category), and 0% (very less category) and cycle II increased to 65 % (very good category), 25% (good category), 10% (enough category), 0% (less category), and 0% (very less category). Student learning outcomes cycle I learning mastery reaches 70% and cycle II increased to 90%. From the exposure of these data can prove that the use of paragraph media board can improve the activity and learning outcomes of IPS in the material struggle of the Indonesian nation against the invaders in class V SDN Pasanggrahan I Sumedang Selatan District Sumedang Sumedang Year 2016/2017